2017
DOI: 10.2139/ssrn.3067596
|View full text |Cite
|
Sign up to set email alerts
|

On Matching and Thickness in Heterogeneous Dynamic Markets

Abstract: We study dynamic matching in an infinite-horizon stochastic market. While all agents are potentially compatible with each other, some are hard-to-match and others are easy-to-match. Agents prefer to be matched as soon as possible and matches are formed either bilaterally or indirectly through chains. We adopt an asymptotic approach and compute tight bounds on the limit of waiting time of agents under myopic policies that differ in matching technology and prioritization.We find that the market composition is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…27 We also examined weighted optimization using various weights and found no any qualitative differences. This is consistent with Ashlagi et al (2019), which found that prioritization is negligible when there are more hard-to-match We also compute the average matching time and waiting time for different types of pairs. match only with over-demanded pairs.…”
Section: Empirical Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…27 We also examined weighted optimization using various weights and found no any qualitative differences. This is consistent with Ashlagi et al (2019), which found that prioritization is negligible when there are more hard-to-match We also compute the average matching time and waiting time for different types of pairs. match only with over-demanded pairs.…”
Section: Empirical Findingssupporting
confidence: 85%
“…waiting time, as the compatibility probability tends to zero. 11 Ashlagi et al (2016) add asymmetric types to this random compatibility model where one type has a non-vanishing probability of being matched with any other agent. In particular, in contrast to our model, any two types can potentially match.…”
Section: Related Literaturementioning
confidence: 99%
“…We identified a unique breaking point where a stark reduction in matching cost compared to a stark increase in waiting cost occurs. In line with recent works by Ashlagi et al (2017), Ashlagi et al (2018) and many others, we focused on a concrete class of social welfare functions that weigh costs from waiting versus matching on a comparable scale and identify the optimal clearing schedule, namely, the clearing schedule that matches the k-th couple when Θ( √ k(log k) 1/3 ) players are on the short side of the market.…”
Section: Discussionmentioning
confidence: 98%
“…Emek et al (2019) obtain sharper results for a two-location model. There are also other extensions such as allowing for a stochastic graph (Anderson et al, 2015;Ashlagi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Related literature The paper contributes mainly to three strands of the literature. The first strand is the literature on market design, which studies dynamic matching markets such as those in this paper, but from the point of view of optimality instead of stability (Ünver (2010), Leshno (2017), Akbarpour et al (2017), Anderson et al (2015), Schummer (2015), Bloch and Cantala (2017), Ashlagi et al (2018), Arnosti and Shi (2018), Baccara et al (2019), Thakral (2019)). The present study of stability is important because stability is considered a key property for the success of algorithms (Roth (1991)) and because it highlights the potential issues in applying the static notions of stability to dynamic matching markets.…”
Section: Introductionmentioning
confidence: 99%